Causes of Crime. Uncovering a lay model - Campbell, Anne (Criminal justice and behavior, 1990)
This exploratory study examines the independent variables identified by a group of noncriminologists as being responsible for crime and describes the perceived causal connections between them. Sociological causes are more frequently invoked than are psychological factors. Network analysis reveals an implicit model composed of distal, mediating, and proximal causes. Two subsystems are identified, corresponding to societal and personal crime pathways. They are united by the perceived relationship between poverty and drug use